Dampak Harga Emas Dunia Tingkat Suku Bunga Acuan dan Inflasi terhadap Jakarta Islamic Index - Rajwa Rajendra Sudarsana; Muhammad Yusuf; Puji Yuniarti (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the impact of changes in world gold prices, interest rate, and inflation on the value of Jakarta Islamic Index (JII). JII is a Sharia stock index comprising 30 Sharia-compliant stocks with the largest average daily transactions in Indonesia. This index serves as an important representation of Indonesia's Sharia-based capital market. By utilizing macroeconomic variables such as world gold prices, interest rate, and inflation, this research is expected to provide insights to relevant parties regarding the impact of these variables on the Sharia stock index in Indonesia. This study employs a quantitative approach using secondary monthly data from January 2015 to December 2023. This study use Generalized Autoregressive Conditional Heteroscedasticity (GARCH) model to provide an accurate depiction consistent with the research model and the characteristics of the data used. The analysis results indicate that the world gold price variable has a significant negative effect on Jakarta Islamic Index (JII). The inflation variable has a significant positive effect on JII. Meanwhile, interest rate has a negative but statistically insignificant effect on JII. This data analysis model can explain 44.8% of the determination coefficient, while the remainder is influenced by other factors outside the model.